How to select good leaders in Asian countries: the case of China and Singapore - Franky K.H. Choi (Public Administration and Policy, 2021)
Purpose – The purpose of this paper is to bring out the possibility of selecting good leaders in Asian countries, i.e., China and Singapore. Design/methodology/approach – Since comparative historical analysis enhances the objectivity for academic discussion, Deng Xiaoping’s and Lee Kuan Yew’s leadership successions have been chosen as the cases for studies by virtue of “method of agreement”. Incorporating “argument based on the contrary” into the context for macro-historical analysis, this paper characterises the duo’s successful (at least quite successful) leadership successions, thus offering an alternative paradigm beyond Western-style democracy. Findings – Both cases of post-Mao China and the independent Singapore indicate that in quite a number of Asian countries, good leaders could still be selected beyond universal suffrage as practised among Western Electoral Democracies, mainly because of the elites-driven context. As to the duo’s succession results, Deng Xiaoping’s selection of leaders was somewhat successful, while Lee Kuan Yew’s was phenomenal. Originality – This paper offers readers a glance over the possibility of selecting good leaders in Asian countries not fully based on Western-style democracy. Learning from the duo’s leadership successions, the West may treat elite politics as the supplement under Western Electoral Democracies in order to avoid their countries falling into the trap of populism. The West could meanwhile consider the exceptional criteria prized by the duo for leadership successions. Considering such interactions among elites in the real-life context, it could serve as an alternative model to Western-style democracy.